Automation process in data collection for representing façades in building models as part of the renovation process - Kepa Iturralde; Peru Elguezabal; Asier Mediavila (Journal of Facade Design and Engineering, 2023)
A key barrier in building-facade renovation processes is that, contrary to new designs, an initial building model where the design process is based rarely exists, and the technologies usually employed to create it (e.g., based on point cloud scanning) are costly or require modeling skills. This situation is a clear limitation, especially in early decision stages, where the level of detail required is not very high, and the analysis and studies to consider the renovation plan (e.g., simplified energy simulations and renovation potential, or estimation of the number, types, and dimensions of the prefabricated modules incorporating solar panels) highly depend on such digital models. This paper introduces a process that, based on freely available data such as open GIS sources (local Cadasters, OpenStreetMap…) and façade images, can semi-automatically generate the 3D building model of the existing conditions, and in a second step also suggests the prefabricated facades module layout for building upgrades. Additionally, no onsite visit is needed. When the upgrade is focused on the façade, a big opportunity is identified for generating the building model and a realistic representation of its envelope, only using online data sources as input. The process developed consists of a set of easy-to-use software tools that can be used independently or combined in a workflow, depending on the available data and starting conditions. Time saving is very clear and costs can be reduced.